1991
DOI: 10.1159/000182159
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Clonidine and Growth-Hormone-Releasing Hormone on Growth Hormone Secretion in Patients with Hyperthyroidism

Abstract: Patients with hyperthyroidism have reduced growth hormone (GH) responses to pharmacological stimuli and reduced spontaneous nocturnal GH secretion. The stimulatory effect of clonidine on GH secretion has been suggested to depend on an enhancement of hypothalamic GH-releasing hormone (GHRH) release. The aim of our study was to evaluate the effects of clonidine and GHRH on GH secretion in patients with hyperthyroidism. Eight hyperthyroid females with recent diagnosis of Graves’ disease (age range 20–55 years, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Moreover, in hyperthyroidism peak GH values after GHRH were also blunted, confirming earlier studies [25][26][27]. However, surprisingly, we also found a decrease in GH response to GHRP-6, which is in contrast to our previous report showing normal GH response to GHRP-6 associated with blunted GH responsiveness to GHRH in thyrotoxicosis [28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, in hyperthyroidism peak GH values after GHRH were also blunted, confirming earlier studies [25][26][27]. However, surprisingly, we also found a decrease in GH response to GHRP-6, which is in contrast to our previous report showing normal GH response to GHRP-6 associated with blunted GH responsiveness to GHRH in thyrotoxicosis [28].…”
Section: Discussionsupporting
confidence: 90%
“…Impaired GH release has been found in patients with thyroid dysfunctions [22]. In hyperthyroidism a blunted GH response to several pharmacological stimuli, such as GHRH, has been demonstrated [24][25][26][27]. We have previously shown that GH response to GHRP-6 is normal in thyrotoxicosis while GH responsiveness to GHRH is decreased [28].…”
Section: Introductionmentioning
confidence: 96%
“…A decrease in circulating T3 could interfere with GH secretion at hypothalamic and/or pituitary level. It has previously been suggested that an increase in hypothalamic somatostatinergic tone could participate in the blunted GH response to pharmacological stimuli in thyrotoxicosis ( Giustina et al ., 1990 , 1991; Valcavi et al ., 1992 ). Indeed, it has been shown that T3 increases somatostatin release from rat hypothalamic fragments in vitro ( Berelowitz et al ., 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired GH release has been found in patients with thyroid disturbances. In hyperthyroidism, a blunted GH response to several pharmacological tests, such as GHRH, has been found ( Burgess et al ., 1966 ; Giustina et al ., 1991 , 1992; Valcavi et al ., 1993 ; Ramos‐Dias et al ., 1995 ). The mechanisms involved in this alteration have not been fully elucidated.…”
mentioning
confidence: 99%
“…The GH response to GHRH in hyperthyroid patients has also been reported to be blunted [9,12], Moreover, pharmacologi cal substances thought to stimulate endogenous GHRH secretion, such as clonidine [23] and galanin [24]. are not able to reverse GH inhibition in hyperthyroidism [25,26] Arginine is a well-known GH secretagogue [13]. Re cently, the mechanism through which arginine stimulates GH secretion has been elucidated.…”
Section: Discussionmentioning
confidence: 99%